Parameter Optimization of Transformer Model Based onSimulation Credibility Evaluation - YING Ting; LI Jianghong (Kongzhi Yu Xinxi Jishu)
In order to explore an effective method to enhance the credibility of simulation system, this paper proposes a model parameter optimization method based on simulation credibility evaluation. Traction transformer is selected as the research object. The concept of simulation credibility is introduced, and the quantitative error of simulation and test data is taken as the optimization objective. At the same time, the input signal is selected according to the demand of solving the optimization problem, and the optimization parameters are selected according to the sensitivity analysis results, and an optimization model is established to optimize the key parameters. Simulation reliability of the optimized results has been greatly improved in both quantitative and qualitative analysis, which proves the effectiveness of the research content in this paper.